Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Kinerja Karyawan: Sebuah Studi Literatur - Diah Pitaloka Puspitasari; Hafid Kholidi Hadi (BIMA : Journal of Business and Innovation Management, 2020)
In achieving the company's main objectives seen from the ability and achievement of employee performance. This achievement involves emotional intelligence and spiritual intelligence at work. Studies of emotional intelligence and spiritual intelligence on performance have been carried out by many researchers before, but the results obtained vary greatly. Therefore, the purpose of this study is to study and analyze the results of previous studies in the field of industrial organizations, which are related to the meta-analysis study approach. The meta-analysis study was conducted by reviewing 16 studies based on the results of the selection of the correlation value r, the reliability coefficient, the characteristics of the research subjects, and were the primary studies. Based on the results of the analysis that has been done, empirically the results of literature studies with this meta-analysis are able to answer while convincing researchers that emotional intelligence and spiritual intelligence are the most important things in increasing their participation in decision making and can create an active work atmosphere.